Biochemical Impact of Dexmedetomidine on Inflammatory and Stress Markers in Gastric Cancer Surgery: A Meta-Analysis: Serum Markers in Dexmedetomidine Anesthesia - Zhang, Xuhui; Hu, Wenjun; Wang, Jinghua; Qin, Rui; Wang, Xinlei; Zhang, Zhenhua (Journal of Medical Biochemistry, 2025)
Background: Dexmedetomidine, an α2-adrenergic agonist, has been reported to modulate inflammatory responses and neuroendocrine stress in surgical settings. This meta-analysis evaluated its effects on serum biochemical markers of inflammation and stress in patients undergoing gastric cancer surgery.Methods: Literature was retrieved from PubMed, CNKI, Wanfang, and VIP databases. Studies comparing dexmedetomidine anesthesia with conventional regimens in gastric cancer surgery were included. RevMan 5.2 was used for meta-analysis. Outcome indicators included interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), cortisol, epinephrine, adrenocorticotropic hormone (ACTH), heart rate (HR), mean arterial pressure (MAP), and adverse events.Results: Fifteen studies were analyzed. Compared with controls, dexmedetomidine significantly reduced serum levels of IL-6, TNF-α, cortisol, epinephrine, and ACTH (all P < 0.00001). It also decreased HR, MAP, visual analog scale (VAS) scores, and incidence of adverse reactions.Conclusion: Dexmedetomidine anesthesia effectively reduces biochemical markers of inflammation and stress in gastric cancer surgery, suggesting its beneficial role in modulating perioperative biochemical responses.
Keywords: Dexmedetomidine; Inflammatory markers; Stress hormones; Gastric cancer; Meta-analysis; Biochemical modulation